The Arabidopsis SHORTROOT network coordinates shoot apical meristem development with auxin-dependent lateral organ initiation - Bahafid, Elmehdi; Bradtmöller, Imke; Thies, Ann M; Nguyen, Thi TON; Gutierrez, Crisanto; Desvoyes, Bénédicte; Stahl, Yvonne; Blilou, Ikram; Simon, Rüdiger GW (eLife, 2023)
Plants produce new organs post-embryonically throughout their entire life cycle. This is due to stem cells present in the shoot and root apical meristems, the SAM and RAM, respectively. In the SAM, stem cells are located in the central zone where they divide slowly. Stem cell daughters are displaced laterally and enter the peripheral zone, where their mitotic activity increases and lateral organ primordia are formed. How the spatial arrangement of these different domains is initiated and controlled during SAM growth and development, and how sites of lateral organ primordia are determined in the peripheral zone is not yet completely understood. We found that the SHORTROOT (SHR) transcription factor together with its target transcription factors SCARECROW (SCR), SCARECROW-LIKE23 (SCL23) and JACKDAW (JKD), promotes formation of lateral organs and controls shoot meristem size. SHR, SCR, SCL23, and JKD are expressed in distinct, but partially overlapping patterns in the SAM. They can physically interact and activate expression of key cell cycle regulators such as CYCLIND6;1 ( CYCD6;1 ) to promote the formation of new cell layers. In the peripheral zone, auxin accumulates at sites of lateral organ primordia initiation and activates SHR expression via the auxin response factor MONOPTEROS (MP) and auxin response elements in the SHR promoter. In the central zone, the SHR-target SCL23 physically interacts with the key stem cell regulator WUSCHEL (WUS) to promote stem cell fate. Both SCL23 and WUS expression are subject to negative feedback regulation from stem cells through the CLAVATA signaling pathway. Together, our findings illustrate how SHR-dependent transcription factor complexes act in different domains of the shoot meristem to mediate cell division and auxin dependent organ initiation in the peripheral zone, and coordinate this activity with stem cell maintenance in the central zone of the SAM.